Global Environment Outlook - GEO-6: Technical Summary - UN Environment (Cambridge : Cambridge University Press, 2021)
The sixth Global Environment Outlook was launched in 2019 at the fourth UN Environment Assembly. It highlighted the ongoing damage to life and health from pollution and land degradation, and warned that zoonosis was already accounting for more than 60% of human infectious diseases. Since then the spread of COVID-19 has demonstrated the enormous challenges a global pandemic can cause for health care systems and the economy, as well as revealing potential environmental benefits of an altered lifestyle. This Technical Summary synthesizes the science and data in the GEO-6 report to make it accessible to a broad audience of policymakers, students and scientists. It demonstrates that more urgent and sustained action is required to address the degradation caused by our energy, food and waste systems and identifies a variety of transformational pathways for those seeking far-reaching policies for environmental and economic recovery. Also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 02 Dec 2020).